Risk Alleles for Multiple Sclerosis Identified by a Genomewide Study - Hafler, David A; Compston, Alastair; Sawcer, Stephen; Lander, Eric S; Daly, Mark J; De Jager, Philip L; de Bakker, Paul I W; Gabriel, Stacey B; Mirel, Daniel B; Ivinson, Adrian J; Pericak-Vance, Margaret A; Gregory, Simon G; et al. (The New England journal of medicine, 2007)
A large genomewide association study of multiple sclerosis uncovered a number of single-nucleotide polymorphisms that have a strong statistical association with the disease. Of these allelic variants, the three with the strongest association relate to immunologic elements: a gene in the HLA region and alleles of IL2RA and IL7RA . Both IL2RA and IL7RA have been implicated in other autoimmune diseases. A large genomewide association study of multiple sclerosis uncovered a number of single-nucleotide polymorphisms that have a strong statistical association with the disease. Multiple sclerosis, the most common neurologic disease affecting young adults, is an inflammatory, presumed autoimmune disorder in which lymphocytes and macrophages infiltrate the central nervous system, 1 – 3 sometimes together with antibodies and complement. 4 , 5 Axonal transection with neuronal loss can be an early event in the disease. 6 Systemically, there is subtle dysregulation of cellular and humoral immune responses with a loss of regulatory T-cell function. 7 Studies of twins and sibling pairs suggest that genetic factors influence susceptibility to multiple sclerosis; the evidence indicates that multiple genes, each exerting only modest effects, probably play a part. 3 , 8 Candidate-gene studies have validated . . .